2020
DOI: 10.1128/jcm.02083-19
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Candida auris Outbreak Provides New Insights into an Emerging Pathogen

Abstract: Candida auris is an emerging human fungal pathogen that is being increasingly linked to outbreaks. It is concerning to health care workers because of its high mortality rate, due primarily to its antifungal resistance. Among the tools being developed to study this yeast are large cohorts of regional isolates, which can be useful for studying epidemiology, antifungal susceptibility patterns, and diagnostic methods. In this issue of the Journal of Clinical Microbiology, Y. Zhu, B. O’Brien, L. Leach, A. Clarke, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…Rapidly identifying patients with C. auris colonization in healthcare facilities is critical for implementation of proper infection-control measures to contain the spread. Swabs of nares, axilla and groin were identified as the high-yield body sites for identifying C. auris-colonized patients [6]. A realtime PCR assay testing for C. auris in patient surveillance samples has been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapidly identifying patients with C. auris colonization in healthcare facilities is critical for implementation of proper infection-control measures to contain the spread. Swabs of nares, axilla and groin were identified as the high-yield body sites for identifying C. auris-colonized patients [6]. A realtime PCR assay testing for C. auris in patient surveillance samples has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of C. auris hospital outbreaks revealed that patients infected with C. auris harboured the organism at multiple body sites, including nares, groin, axilla and rectum 1 to 3 months after initial detection of C. auris, and persistence of the organism in the patient room could be detected 3 months after patient discharge [5]. Nares, axilla and groin were identified as high-yield body sites for identifying colonized patients [6]. Assays for C. auris surveillance need to work with a common sample transportation medium for patient and environmental sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Candida auris is an emerging fungal pathogen reported on all continents except Antarctica, in at least 39 countries worldwide [ 1 ], as well as in 20 states of the United States [ 2 , 3 , 4 , 5 ]. Five distinct clades of C. auris were identified with well-defined geographic distributions (South America, Africa, South Asia, East Asia, and West Asia), as well as antifungal resistance patterns and mechanisms that are both distinct and unique [ 1 , 6 , 7 , 8 ]. Infections due to C. auris are most often nosocomial, with easy transmission from patient-to-environment and environment-to-patient [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Timely and accurate diagnosis of invasive candidiasis are important for early initiation of antifungal therapy, while species identification is critical to ensure implementation of infection control measures [ 1 , 6 , 10 , 11 ]. Acceptable standard diagnostic methods for C. auris identification include matrix-assisted laser desorption ionization–time of flight (MALDI-TOF) and VITEK2™ with the appropriate updated databases and DNA sequencing [ 7 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…C. auris is a multidrug-resistant pathogen that has been identified in 39 countries and has spread across five continents, with a mortality rate of ~78% [ 3 ]. Furthermore, risk factors that aggravate C. auris infections include conditions such as diabetes mellitus, cardiovascular surgical interventions and gastrointestinal pathologies, hematological malignancies and even corticosteroid therapy [ 4 ].…”
Section: Introductionmentioning
confidence: 99%